Transformational Leadership in Public Sector Innovation: A Bibliometric Analysis - Setiyatmo Adi Nugroho; Muh Azis Muslim (Asian Journal of Social and Humanities, 2024)
People and organizations need to adapt to rapidly evolving technology and information trends, but are often faced with limited resources. Therefore, innovation is important to be applied to various sectors, including the public sector which is known for the many regulations that surround it. Innovation is seen as a source of change, growth, and organizational effectiveness, but leadership factors have a dominant impact and are fundamentally critical to success in achieving it. This study aims to see trends in scientific publications (journals) regarding transformational leadership in public sector innovation; the most influential journals and authors; as well as potential research topics in the future. This study uses bibliometric analysis taken from the database of highly reputable journals Scopus by looking at the analysis results from the Scopus web on data that has been filtered according to criteria; visualization and analysis of data using VOS viewer application as well as biblioshin application. Based on the results of the study, the research topic of Transformational Leadership in Public Sector Innovation is still little discussed in Scopus indexed journal publications. The data obtained also shows that in the middle of the last 5 years, the topic shows the significance of increasing the quantity of publications which increasingly shows the interest of the theme of transformational leadership in public sector innovation with the times.